2015
DOI: 10.1149/2.0701504jes
|View full text |Cite
|
Sign up to set email alerts
|

Self-Combustion Synthesis and Ion Diffusion Performance of NaV6O15Nanoplates as Cathode Materials for Sodium-Ion Batteries

Abstract: NaV 6 O 15 nanoplates are successfully prepared by a facile and low-cost self-combustion method, which can be considered as promising cathode materials for high capacity sodium-ion batteries (NIBs). Morphology analysis suggests that the self-combustion method leads to the NaV 6 O 15 nanoplates possessing uniform size, with an average length of 400 nm and width of 100 nm. As the cathode materials, the NaV 6 O 15 nanoplates exhibit a high initial discharge specific capacity of 149.48 mAh g −1 at a current densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…This finding is in good correlation with the slight interlayer contraction combined with the increasing amount of Na. Scarce data are available on Na + mobility in sodiated oxides and bronzes, with very close values in the range 10 −12 –10 −10 cm 2 s −1 reported for Na 0.33 V 2 O 5 ,, Na x CoO 2 , and P2‐Na 0.67 MnO 2 …”
Section: Resultsmentioning
confidence: 99%
“…This finding is in good correlation with the slight interlayer contraction combined with the increasing amount of Na. Scarce data are available on Na + mobility in sodiated oxides and bronzes, with very close values in the range 10 −12 –10 −10 cm 2 s −1 reported for Na 0.33 V 2 O 5 ,, Na x CoO 2 , and P2‐Na 0.67 MnO 2 …”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20] At present, many types of synthesis methods for NaV 6 O 15 (b-Na 0.33 V 2 O 5 ), such as solid-state reaction, 21 sol-gel method 22 and hydrothermal method, 23,24 have been attempted to improve its electrochemical performances. Among various morphologies of NaV 6 O 15 structures, nanosheets, 25 microspheres 26 and nanoakes, 27 can improve electrochemical performance of the batteries further. For example, Lu et al reported hydrothermal synthesis of b-Na 0.33 V 2 O 5 nanosheets, which exhibited a discharge capacity of 258 mA h g À1 at the current density of 150 mA g À1 and the capacity retention of 70.2% aer 50 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Shinde et al, used the ultrasonic sonochemical synthesis method to prepare Na 0.44 MnO 2 cathode, which shows the reversible capacity of about 110 mAhg −1 at a current rate of C/10 with good cycling stability [62]. By changing the preparation method to self-combustion, the NaV 6 O 15 nanoplates show the capacity of about 150 mAhg −1 at a current rate of 20 mAg −1 , which remains about 82 mAhg −1 after 30 cycles [53]. On the other hand, NaV 6 O 15 nanorods prepared by PVP-modulated synthesis route shows high initial capacity of about 157 mAhg −1 at 20 mAg −1 current density [41].…”
Section: Structural Analysismentioning
confidence: 99%
“…39,49,58,59 Jiang et al synthesized NaV 6 O 15 nanoplates and reported a discharge capacity of 116 mAh g –1 measured vs Na + /Na with a cycle retention of 55% at a current density of 50 mA g –1 . 58 However, note that the electrochemical performance of Na 0.33 V 2 O 5 critically depends on the synthesis conditions, size in nanometer, and morphology. 39,49,58,59 Therefore, nanostructures of Na 0.66 V 4 O 10 [(Na 0.33 V 2 O 5 ) 2 ] in different morphologies still need to be explored in detail as cathode material for Na-ion batteries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation